2021
DOI: 10.1007/s10198-021-01287-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping PedsQL™ Generic Core Scales to EQ-5D-3L utility scores in transfusion-dependent thalassemia patients

Abstract: Purpose To develop a mapping algorithm for generating EQ-5D-3L utility scores from the PedsQL Generic Core Scales (PedsQL GCS) in patients with transfusion-dependent thalassemia (TDT). Methods The algorithm was developed using data from 345 TDT patients. Spearman's rank correlation was used to evaluate the conceptual overlap between the instruments. Model specifications were chosen using a stepwise regression. Both direct and response mapping methods were attempted. Six mapping estimation methods ordinary leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In the existing mapping research of Peds QL 4.0, the Peds QL 4.0 total score, the Peds QL 4.0 dimension scores, and the Peds QL 4.0 item scores were often used as independent variables ( 19 21 , 24 ), as well as some demographic indicators such as age and gender. We screened the independent variables according to the correlation between the variables (see Appendix 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the existing mapping research of Peds QL 4.0, the Peds QL 4.0 total score, the Peds QL 4.0 dimension scores, and the Peds QL 4.0 item scores were often used as independent variables ( 19 21 , 24 ), as well as some demographic indicators such as age and gender. We screened the independent variables according to the correlation between the variables (see Appendix 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to several other studies, almost all the estimators overestimated the lower bound of the CHU-9D utility score and overpredicted the upper bound of 1 ( 21 , 22 ). Although overprediction is a difficult problem, some studies have shown that it can be dealt with by truncating or setting the value of the dependent variable between 0 and 1 to the boundary value, such as Tobit model and Beta model ( 24 , 53 , 54 ). Overall, the predictive performance of the Beta model and Tobit model was consistent with the MAE range (0.0408–0.1270) and RMSE range (0.0594–0.1619) observed in the CHU-9D mapping study ( 19 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PedsQL™ scores could not be used to calculate a quality adjusted life years (QALY) outcome directly as it is a non‐preference‐based measure (NPBM) instrument 23 . Therefore, a mapping algorithm was adopted to convert the scores of PedsQL™ to the utility score of the EQ‐5D‐Y (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have found correlations between PedsQL and EQ-5D-Y-3L and CHU9D and often use PedsQL as a gold standard for convergent validity in validation studies [ 4 , 13 17 ]. There are mapping algorithms to infer EQ-5D and CHU9D utility scores from PedsQL [ 18 20 ]. Although our study focuses on providing evidence for validation for descriptive system for PBMs instead of utility (i.e., a single index which gives limited information on different health dimensions), the mapping algorithm added evidence to the common concept between PedsQL and EQ-5D-Y and CHU9D.…”
Section: Introductionmentioning
confidence: 99%